2019
DOI: 10.1111/joa.13136
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of the inferomedial orbital strut using a standardized three‐dimensional printing implant

Abstract: The inferomedial orbital strut (IOS) is the thin bony junction of the orbital medial wall and floor. Its fracture is common and leads to serious complications, including enophthalmos, globe dystopia and diplopia. However, anatomical restoration of the IOS is challenging owing to reduced structural support; sound anatomical background and accurate implants are therefore essential. The aim of the present study was to incorporate data from cadaveric orbit anatomy into three-dimensional (3D) printing technology an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 40 publications
(53 reference statements)
0
11
0
Order By: Relevance
“…In recent years, patient-specific implants have shown good surgical results [ 20 ]. Most customized implants are based on the shape of the orbital floor on the normal side and the mirroring technology is used to reconstruct the orbital floor on the fracture side [ 34 ]. However, sometimes the orbital volume is undercorrected or overcorrected after surgery, which may be due to the fact that the patient customizing plate is not corrected as planned, or because the shape of the orbits on both sides is different [ 5 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, patient-specific implants have shown good surgical results [ 20 ]. Most customized implants are based on the shape of the orbital floor on the normal side and the mirroring technology is used to reconstruct the orbital floor on the fracture side [ 34 ]. However, sometimes the orbital volume is undercorrected or overcorrected after surgery, which may be due to the fact that the patient customizing plate is not corrected as planned, or because the shape of the orbits on both sides is different [ 5 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Various clinical applications of 3D-printed PCL implant have been reported in the management of cleft alveoli, augmentation rhinoplasty, nasal septal deformity, orbital wall reconstruction, and complex maxillary defect [11,[19][20][21][22][23]. In the case of a cleft alveolus, the PCL scaffold with human bone marrow cells was found to have a newly regenerated bone volume that was approximately 45% of the total defect volume at 6 months after implantation [11].…”
Section: Discussionmentioning
confidence: 99%
“…In cases of nasal septal deformities, a multicenter clinical trial of 20 patients with septal deviations that were managed using 3D-printed PCL implant, it was found that PCL implant provided proper mechanical support and had excellent biocompatibility and surgical manipulability [20]. In an inferomedial orbit implant, five implants showed no extrusions and structural stabilities during the mean follow-up period of 20.8 (18)(19)(20)(21)(22)(23)(24)(25)(26)(27) months [21]. In the cases of three complex maxillary defects, the PCL scaffold was stable in the maxillary defect and promoted regeneration of the deficient tissues in 2 years [22].…”
Section: Discussionmentioning
confidence: 99%
“…Combined inferior and medial wall fractures pose a particular challenge given destruction of the inferomedial orbital strut. Kim et al used 100 cadaver skulls to create a digital model of a standardized inferomedial orbital strut used in 3D printing of polycaprolactone implants [ 83 ]. Interlocking puzzle-piece implants can be used to bridge two or more implants across missing landmarks in cases of adjacent wall fractures; doing so may reduce incisional burden by enabling piece-by-piece placement through the same incision [ 84 87 ].…”
Section: Methodsmentioning
confidence: 99%